China interest in Latin America - Aquino Rodríguez, Carlos Alberto (2016)
The interest of China in Latin America has increased and it is planning to double its trade and investment with the region by the year 2025.In this article we analyze the latest developments regarding China interest in the región and in the case of Peru we see an increasing interest of China in investment in the primary sector, Also the possibiity of Peru becoming a hub of China in the region is analyzed. Besides, the growing interest of China in investment in other áreas, as in infrastructure, nuclear energy and agriculture is showed.